Plant CDC2 is not only targeted to the pre-prophase band, but also co-localizes with the spindle, phragmoplast, and chromosomes - Stals, Hilde; Bauwens, Serge; Traas, Jan; Van Montagu, Marc; Engler, Gilbert; Inzé, Dirk (FEBS letters, 1997)
A polyclonal antiserum against the p34 cdc2 homologue of Arabidopsis thaliana, CDC2aAt, was used in parallel with a polyclonal antiserum against the PSTAIRE motif to study the subcellular localization of CDC2 during the cell cycle of isolated root tip cells of Medicago sativa. During interphase, CDC2 was located in the nucleus and in the cytoplasm. The cytoplasmic localization persisted during the complete cell cycle, whereas the nuclear signal disappeared at nuclear envelope breakdown. At the beginning of anaphase, the anti-CDC2aAt antibody transiently co-localized with condensed chromosomes. The chromosomal co-localization disappeared as anaphase continued and remained excluded from the separated chromosomes until cytokinesis, when CDC2 re-located to the newly forming nuclei. We also observed a co-localization of CDC2 with three microtubular structures, the pre-prophase band, the spindle, and the phragmoplast.